Etiologies of excessive gingival display in a Saudi population - Reham AL Jasser; Rand AlSaif; Loulwah AlSohaim; Raghad Baidas; Faiza AL AlOtibi; Reem Andijani (Saudi Dental Journal)
Introduction: Excessive gingival display (EGD) is a mucogingival deformity characterized by overexposure of the maxillary gingiva while smiling. This cross-sectional study aimed to identify EGD etiologies and their prevalence in participants at King Saud University, Saudi Arabia. Methods: Adults with a gummy smile, who resided in Saudi Arabia, were nonsmokers, had good overall health, and had all their maxillary anterior teeth were eligible for inclusion. Participants were first screened by phone, and those who met the eligibility criteria were further screened at the Dental University Hospital (King Saud University, Riyadh, Saudi Arabia). The demographic characteristics of all eligible participants were recorded. Participants were further subjected to extraoral examination, which included gingival display (GD), vertical maxillary excess (VME), hypermobile upper lip (HUL), smile line, altered passive eruption (APE), gingival overgrowth, and short upper lip (SUL). Intraoral examination included periodontal pocket depth and bleeding upon probing. Student’s t-test was used to compare the mean GD values across the main etiologies (VME, HUL, APE, and SUL). Results: All 123 participants (mean age: 23.1 ± 0.2 years; 74 females) had EGD (i.e., GD ≥ 4 mm), of whom 55 (44.7 %) had a single etiology, and the remaining 68 (55.3 %) had > 1 etiology. APE was the predominant etiology (n = 90, 73.2 %) in the study population. Of these (n = 90), APE alone was prevalent in 29 (32.2 %) participants, whereas the remaining patients had APE in combination with other EGD etiologies (n = 61; 67.8 %). The presence of more than one EGD etiology in the same participant was associated with greater GD. The VME and HUL were significantly associated with smile line classes (p < 0.05). Conclusions: APE (alone or in combination) was the predominant etiology of EGD in the study population. The presence of multiple EGD etiologies in the same patient emphasizes the need for an etiology-based, sequential, and multiple-treatment strategy to effectively manage EGD.